Evaluation of fruit quality of old apple cultivars originating from the foot of the Carpathian Mountains, for utilization in breeding and in organic farming - Tóth, M.; Balikó, E.; Szani, Zs. (International Journal of Horticultural Science, 2005)
In the frame of the apple breeding program at the Department of Fruit Science old cultivars found in the Carpathian basin were involved in examination as well. Beside testing susceptibility to fire blight (Erwinia amylovora of old genotypes (historical, local and regional cultivars) originating from scattered orchards of Visk (foot of the Carpathian Mountains), fruit quality was also evaluated and other open-field observations were made. According to the results of inner content examinations, ’Szemes alma’ and ’Sikulai alma’, chosen as gene sources for breeding to resistance against fire blight, had inner content values worthy to mention in some aspects, and competing with those of the control cultivar ’Jonathan’. The quality of ’Pónyik alma’, also recommended as a gene source is confirmed by the data of earlier literature. Further three cultivars (’Batul’, ’Vilmos renet’, ’Zöld sóvári’) also proved to be good based on resistance against Erwinia amylovora, the first two cultivars are suitable from the point of view of fruit quality, too. In our field observations, susceptibility to apple scab and powdery mildew was evaluated. Among cultivars selected from the foot of the Carpathian Mountains on the base of resistance against Erwinia amylovora, the production value of ’Szemes alma’ is worsened by its high susceptibility to apple scab. Further selected cultivars (’Sikulai’, ’Pónyik alma’, ’Batul’, ’Vilmos renet’) are not too susceptible to fungal diseases and their fruit quality is also suitable, therefore they can be recommended for direct planting in ecological farming or in restoring scattered orchards.